WORD FORMATION PROCESS OF GEN Z SLANG IN CALLAHAN'S GENERATION Z DICTIONARY - Kartin Lihawa; Muziatun Mukaji; Sri Rahayu Malingkas; Hasanuddin Fatsah (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2021)
Slang, either the form or the meaning is flexible and temporary, which canchange anytime depending on the user. This phenomenon also occurs in the trendy slang used by Gen Z. Therefore, this study aims to find out the types of word formation process in Gen Z slang. It focuses only on Gen Z slang that is in Callahan's Generation Z Dictionary. Further, this study is corpus-based, using qualitative analysis in investigating the types of word formation process in Gen Z slang. To analyze the corpus, there are two steps used that are classifying and interpreting. The finding reveals that there are eight types of word formation process, which influence in forming the Gen Z slang. Those types are fanciful formation, compounding, blending, clipping, conversion, suffixation, multiple process, and reduplicatives. Among those types, compounding is the most used. There are ten slang terms come through this types of process and this study presents all types of compounding. Those types are compound noun with one slang term, compound adjective with five slang terms, and compound verb with four slang terms. In conclusion, Gen Z slang is formed through eight types of the word formation process and compounding is the most used.